THE PSYCHOLOGICAL PECULIARITIES OF INTERACTIONS IN THE “TEACHER – PUPIL” SYSTEM - Slobodianyk, Natalia (PSYCHOLOGICAL JOURNAL, 2020)
The article presents the empirical research on interactions in the “teacher – pupil” system. The “interaction” notion is considered as the basic category of philosophy and psychology. Interactions help form an individual’s personal space and its various manifestations; the efficiency and results of many problems resolution depend on space characteristics, on an individual’s willingness and ability to be engaged in joint activities as partnership or cooperation, and on the formed culture of social behaviour. Psychological-pedagogical interactions are a fairly broad phenomenon important for the pedagogical process. Interactions appear at the educational situation, which it consists of two interdependent forms of activity: teaching, or transfer of experience accumulated by humankind; and learning, or receipt of this experience, which is transformed into a pupil’s personal acquisition. Psychological-pedagogical interactions are the core of the educational process; so, it is quite important to study them for the further development of psychological and pedagogical theory and practice. Teachers, psychologists, pupils and parents, united by a common understanding of the goals and objectives, play a special role in interactions. That is why the effectiveness of relationships with pupils is quite important; and many researchers believe than relationships in the education system at the “teacher - pupil” level are the central problem in the pedagogical process. This process becomes really efficient only if there is a psychological contact between teachers and their pupils. “Unfinished sentences” method was used at the performed empirical study. As a result, pupils’ ideas about the most important qualities of a modern teacher were determined as well as the image of a modern pupil from the teacher’s point of view. Pupils mainly described teachers’ presentations of educational material as interesting and clear, perceived teachers’ intelligence and kindness. The teachers believed that the main qualities of modern pupils are regulatory competence (discipline, diligence), as well social and personal competence (such pupils’ personal qualities as goodwill, hardworking, curiosity). According to teachers, the formed academic motivation had a special influence. The studied peculiarities of interactions in the ‘teacher–pupil’ system show the relevance of the examined problem, because the pupil receives at school not only knowledge, but also life-important skills. Their personality, worldview and the first interacting methods are developed at school, to be subsequently realized in adulthood.